If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4d + 2d + -4d + 4 = 3 Reorder the terms: 4 + 4d + 2d + -4d = 3 Combine like terms: 4d + 2d = 6d 4 + 6d + -4d = 3 Combine like terms: 6d + -4d = 2d 4 + 2d = 3 Solving 4 + 2d = 3 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2d = 3 + -4 Combine like terms: 4 + -4 = 0 0 + 2d = 3 + -4 2d = 3 + -4 Combine like terms: 3 + -4 = -1 2d = -1 Divide each side by '2'. d = -0.5 Simplifying d = -0.5
| h(x)=-5t^2+50t+10 | | -3x-4=-5(0)-8 | | -3(0)-4=-5y-8 | | 77.52/8.5 | | (M^11N^3)/(N^2M^6) | | 3y=5x-100 | | 852.99+399.49x=10840.24 | | 7a+9=11 | | 8(x+6)-15= | | -5(0)-4y=10 | | 3+6+x=15 | | 186=6(8x-9) | | 2x^3-3x^2-12x+24=0 | | 5(0)-9=-8y-3 | | 8x-10=5x+4 | | C+a=10 | | 3x=-15/2 | | F(2)=x+2 | | Sqrt(5y-1)=7 | | 5x-9=-8(0)-3 | | -2/3x=14/5 | | 525=-5(-10+5) | | 2x^3+5x^2+5x-4= | | -2/3x=15/5 | | b+c=7 | | 6s(2)+18s=0 | | 3x+3x=33 | | 5/5^4 | | 11+5u=-7+13u | | f(x)=5x^2-10x+7 | | 6x^4+2x^2=0 | | .9(x-1000)/200 |